INFLUENCE OF SERVICE QUALITY REGARDING INTENTTIONS TO REVISIT INTENTION THROUGH PATIENT SATISFACTION AT THE WIYUNG HEALTH CENTER, SURABAYA CITY - Rahmawati, Nor Endah; Wardoyo, Dewie Tri Wijayati; Kistyanto, Anang (Jurnal Bisnis dan Keuangan, 2024)
Public health centers as institutions that provide health services need to have human resources capable of providing good quality services to the community. This research aims to analyze the influence of service quality on patient satisfaction at the Wiyung Health Center, to analyze the influence of service quality on the revisit intention, to analyze the influence of patient satisfaction on the revisit intention, and to analyze whether patient satisfaction mediates the relationship between service quality and revisit intention to Wiyung Health Center. The sampling method used in this research was a survey of patients using accidental sampling with a questionnaire. The population in this study were patients who visited the Wiyung Surabaya Health Center, with a total number of patients taken in December 2023 of 6,484 people, and samples were taken from the population using the Slovin formula of 377 people. Data analysis was carried out using descriptive statistics, with tools used in the research using the Structural Equation Model (SEM) method approach with Partial Least Squares (PLS). Based on the results of data analysis, it was obtained: 1) service quality has a positive and significant effect on patient satisfaction; 2) Service quality has a positive and significant effect on revisit intention; 3) Patient satisfaction has a positive and significant effect on revisit intention; 4) Patient satisfaction has a significant effect mediates the relationship between service quality and revisit intention to Wiyung Health Center. Suggestions for the Wiyung Health Center are: 1) needs to promote through social media and brochures for the health equipment it has; 2) needs to conduct an analysis of material needs and plan the purchase of sufficient health equipment; 3) need to create a Customer Care service; 4) needs to carry out excellent service training.